2016
DOI: 10.1371/journal.pone.0154743
|View full text |Cite
|
Sign up to set email alerts
|

Direct Release of Test Results to Patients Increases Patient Engagement and Utilization of Care

Abstract: An important focus for meaningful use criteria is to engage patients in their care by allowing them online access to their health information, including test results. There has been little evaluation of such initiatives. Using a mixed methods analysis of electronic health record data, surveys, and qualitative interviews, we examined the impact of allowing patients to view their test results via patient portal in one large health system. Quantitative data were collected for new users and all users of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 17 publications
7
144
0
Order By: Relevance
“…In fact, as noted earlier, numerous studies have shown that patients consistently found the test result feature among the most useful [48]. The anxiety that was provoked for a small proportion of patients in one study was effectively mitigated when providers manually released results and included a brief note of interpretation [52,81]. Alternatively, more advanced presentations of test results, with automated interpretation of tests that feature more complex language, could help summarize information for patient portal users without increasing the burden on providers.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In fact, as noted earlier, numerous studies have shown that patients consistently found the test result feature among the most useful [48]. The anxiety that was provoked for a small proportion of patients in one study was effectively mitigated when providers manually released results and included a brief note of interpretation [52,81]. Alternatively, more advanced presentations of test results, with automated interpretation of tests that feature more complex language, could help summarize information for patient portal users without increasing the burden on providers.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study evaluating direct release of test results showed that 80% of all patient portal users viewed test results during the year. Of that group, over 80% noted direct release to be a very useful feature, and 70% felt that the patient portal made their provider more accessible to them [52].…”
Section: Discussionmentioning
confidence: 99%
“…Although directly releasing test results in patient portals appears to be valued by patients in the ambulatory setting 37 and may enhance their engagement, it has the potential to increase patient anxiety and health care use. 38 Our organization chose not to release certain laboratory test results, such as drug testing, pregnancy, tumor markers, and pathology results.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that if elderly patients can view results prior to visiting their physicians, it would allow time to absorb and prepare with valid questions regarding their healthcare. One goal that is noted is that making abnormal test results available to the elderly patient population would improve patient safety by increasing the likelihood of elderly patients following up on the abnormal results [8]. This is believed to increase compliance with this elderly patient population which will have a direct impact on nursing and patient care.…”
Section: Challenges To Health Information Technology (Hit) Adoption Bmentioning
confidence: 99%